Influence of precursor size in the hydrothermal synthesis of cellulose-based carbon nanodots and its application towards solar cell sensitization - Jomar, Jomar C. (Animo Repository, 2019)
The utilization of the abundant yet environmentally polluting green algae as renewable source for new materials is highly desirable. This study presents the utilization of raw cellulose (RC) and cellulose nanocrystals (CNC) extracted from the green algae Cladophora rupestris as precursors for carbon nanodots (CNDs) and its potential use as photosensitizer in solar cell. The results of the hydrothermal treatment of the celluloses afforded spherical CNDs with average dimension of 5.79 ± 1.60 nm (TEM) and having crystalline property (d-spacing of 0.253 ± 0.050 nm) indicating graphitic nature. The size distribution and the ease of the CND formation have been shown to be influenced by the size and morphology of the cellulose precursor. The nanometer-sized crystalline CNCs afforded higher CND yield (54.6 ± 2.71%) compared to the micrometer-sized amorphous RC (37.2 ± 2.76% CND yield). However the size polydispersity of the latter was observed to be narrower at 10.0 ± 3.74 nm (AFM) compared to the former (76.9 ± 73.1 nm; AFM) attributed to clustering or aggregation aided by the presence of hydrophilic functional groups. Indeed, the FT-IR and TOF-SIMs analyses of the CNDs confirmed the presence of hydroxyls, oxides, and carbonyl functional groups that can facilitate the clustering. The CNDs exhibit photoluminescence upon UV irradiation and optical characterization using UV–Vis and Fluorescence Spectroscopy supported the structural and functional group analysis of carbon nanodots. Fabrication of the CND-sensitized solar cell showed the potential of CNDs as photosensitizer albeit in lower yield compared to the positive control. © 2019 Elsevier B.V.